PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI PADA TOKO OSCAR - Rudolf Leonardo Oscar; Ibnu Gunawan; Lily Puspa Dewi (Jurnal Infra, 2013)
Oscar Store is a stationary store which sells many varieties of books and stationaries. The problems occuring are profit and loss calculation, stock calculation and cost of goods calculations.Based on the problems, an application that is able to solve these problems is developed. This application is developed using Microsoft Visual Studio 2005.Net programming language and Microsoft SQL Server 2005 database.Results obtained from applications that have been made, among others, administrative information systems that can create and display selling report, purchasing report, equity report, claim report, inventory report, opname stock report, profit and loss report, and best-seller report. These reports are useful to help viewing transactions that occur within a certain period.